Attending to child agency in paediatric palliative care consultations: Adults' use of tag questions directed to the child. Issue 3 (28th January 2022) - Ekberg, Katie; Ekberg, Stuart; Weinglass, Lara; Herbert, Anthony; Rendle‐Short, Johanna; Bluebond‐Langner, Myra; Yates, Patsy; Bradford, Natalie; Danby, Susan
Abstract: Children's agency in their own lives is increasingly recognised as important, including within paediatric health care. The issue of acknowledging child agency is complex in the context of paediatric palliative care, where children have serious and complex conditions that often impact their ability to verbally communicate with others. This study explores how clinicians and parents/guardians direct talk towards a child patient when they are present in a consultation. Conversation analysis methods were used to examine 74 video‐recorded paediatric palliative care consultations. Detailed turn‐by‐turn examination of the recorded consultations identified the recurrent use of a practice described by linguists as a 'tag question', which follows some statement (e.g. 'he loves that, don't ya'). Both clinicians and parents/guardians often directed these tag questions towards the child patient. Analysis demonstrated how these tag questions: (1) validated the child's epistemic authority over what was being said and (2) made a child's response a possible, but not necessary, next action. The findings are discussed in relation to the sociology of child agency and how this agency is acknowledged and displayed within and through social interaction. This research provides direct evidence of children's competence as informants about their own symptoms.